1979
DOI: 10.1063/1.325710
|View full text |Cite
|
Sign up to set email alerts
|

The interaction process for Ag-Al polycrystalline thin-film couples

Abstract: The mechanism of the interaction of polycrystalline Ag-AI thin-film couples to form Ag 2 Al at temperatures from 107 to 221°C has been studied. Techniques of film characterization included Rutherford backscattering, x-ray diffraction, and SEM. The dependence of the interaction on the grain size of the Ag film (660-7500 A) was measured. An effective activation energy of 0.86+0.05 eV was found. The reaction is believed to occur initially by nucleation and growth of Ag 2 Al grains at Ag grain boundaries at the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

1979
1979
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 5 publications
1
4
0
2
Order By: Relevance
“…They reported that the growth of the intermetallic CuMg 2 phase takes place in two well separated stages: nucleation and lateral growth of the intermetallic along the interface until coalescence is complete, followed by a diffusion limited vertical growth of the same intermetallic phase. A similar behavior has been observed in other multilayer systems such as Al/ Ni, 11,15 Al/ Nb, 9,16,17 Al/ Ag, 18 Al/ Co, 3 Ni/ Si, 7,16 V / Si, 19 or Cu/ Sn. 20 Coffey et al 16 developed a kinetic model that incorporates the two stage model and allowed the simulation of the corresponding calorimetric traces.…”
Section: Introductionsupporting
confidence: 57%
“…They reported that the growth of the intermetallic CuMg 2 phase takes place in two well separated stages: nucleation and lateral growth of the intermetallic along the interface until coalescence is complete, followed by a diffusion limited vertical growth of the same intermetallic phase. A similar behavior has been observed in other multilayer systems such as Al/ Ni, 11,15 Al/ Nb, 9,16,17 Al/ Ag, 18 Al/ Co, 3 Ni/ Si, 7,16 V / Si, 19 or Cu/ Sn. 20 Coffey et al 16 developed a kinetic model that incorporates the two stage model and allowed the simulation of the corresponding calorimetric traces.…”
Section: Introductionsupporting
confidence: 57%
“…The phase of the IMC was characterized as Ag 2 Al (JCPDS 14-0647, P6 3 /mmc space group, a = 0.2885 nm and c = 0.4624 nm, γ = 120°) along the [2110 zone axis by a fast Fourier transform (FFT) of the area marked with a white square in Fig. 7(c) [32,33]. The other light colored regions at the lower left corner were the artifacts such an hole and amorphous layer from the TEM sampling process by ion-beam.…”
Section: Resultsmentioning
confidence: 99%
“…After irradiation, the layer thickness changed slightly. The thickness of the layers containing higher Cu values [layers (1) and (3)] increased and the intermediate aluminium layer (2) thickness decreased. In addition, the Ðrst deposited aluminium layer (4) was virtually not a †ected by the irradiation and the interface sharpness at the transition regions decreased even though there remains a destined interface rather than a broad intermixed region as expected.…”
Section: Resultsmentioning
confidence: 99%
“…thermal spikes12h16). In contrast to IBB experiments, heavy ions with energies of \500 keV are used in IBM experiments, where the incident ion energy is adjusted to enable a mixing process to take place especially at the interfaces of thin layers due to purely ballistic e †ects.17h19 Besides the study of the physical process of interdi †usion, thin metal layers and their interfaces are of practical interest for contacts in microelectronics.20,21 For many devices, contacts are made of aluminium together with other metals1, 2,9,22 and the interface sharpness is an important factor in determining the quality and the performance. 23 Therefore, the knowledge of changes in structure induced by * Correspondence to : A. Markwitz, Forschungszentrum Rossendorf, Institut fu r Ionenstrahlphysik und Materialforschung, Postfach 51 01 19, D-01314 Dresden, Germany.…”
Section: Introductionmentioning
confidence: 99%